DERECHO DEL ADOPTADO AL CONOCIMIENTO DE SUS ORÍGENES BIOLÓGICOS: ¿CUÁLES SON SUS LÍMITES? UNA MIRADA A LA DOCTRINA Y JURISPRUDENCIA COMPARADA - Gonzales Pérez de Castro, Maricela (2022)
There is some discussion about the right of the adoptee to know her/his biological origins. On the one hand, one can speak of an unconditioned fundamental right to have access to true parentage, by the fact of knowing; on the other hand, of a right that, since it is not absolute, can be assigned to other interests that are also legitimate and worthy of protection. In these order of ideas, maternal anonymity, it has been contemplated by many European legal systems, is presented as a limit of such right. By virtue of this, it is intended to safeguard the identity of the biological parents and, above all, the life of the newborns.